A literatura de cordel em sala de aula : uma proposta pedagógica para a construção de um sujeito crítico - Alves, Roberta Monteiro (2010)
The current work is based on the study of the cordel literature in High School classrooms, mainly 9th grader, whose purpose is to subsidize the preparation of subjects and discourses aware of their identity and citizenship. Since contemporary education can no longer live along with the exclusion of popular culture as well as their discursive subjects it is a must that an ever-growing alliance between the teaching-learning process and diversity and cultural identity be utilized so that there will be a decrease in prejudice, not only towards the so called cordel literature , but also the universe that surrounds it. Our methodology consisted of a bibliographical research on history and the formal characteristics of cordel literature; we interviewed three cordel artists from the State of Sergipe two men and one woman so as to make it possible to identify different points of view; we also studied some leaflets under the light of the Discourse Analysis; and finally, we investigated the possibility of its use in classrooms following a pedagogical proposal. In our Conclusion we present our impressions and expectations towards the project s feasibility as our aim in this project was not that of finding flaws in its applicability but to encourage the study of cordel literature in class.